RNA 3D Structure Prediction Using Coarse-Grained Models - Li, Jun; Chen, Shi-Jie (Frontiers in Molecular Biosciences, 2021)
The three-dimensional (3D) structures of RNA molecules are essential to understanding their various and important biological functions. However, experimental determination of the atomic structures is laborious and technically difficult. The large gap between the number of sequences and the experimentally determined structures enables the thriving development of computational approaches to modeling RNAs. However, computational methods based on all-atom simulations are intractable for large RNA systems, which demand long-time simulations. Facing such a challenge, many coarse-grained (CG) models have been developed. Here, we provide a review of CG models for modeling RNA 3D structures, compare the performance of the different models, and offer insights into potential future developments.